Transcriptomic and metabolomic analyses of root responses in Indigofera stachyodes seedlings under drought stress: a medicinal plant native to karst mountainous regions - Ye, Qingqing; Zhang, Na; Tan, Xin; Yang, Li; Ding, Ning; Zhou, Wei; Wu, Zhikun (Frontiers in Plant Science, 2025)
IntroductionIndigofera stachyodes Lindl. is a perennial shrub belonging to the Fabaceae family that has been traditionally utilized as a medicinal plant by ethnic minority groups in Guizhou Province, China. This species exhibits significant ethnopharmacological value in local traditional medicine systems. The plant predominantly inhabits karst mountainous regions characterized by frequent drought stress, which represents a typical harsh habitat for plant growth. Notably, drought conditions particularly impair the establishment and development of I. stachyodes seedlings. However, the molecular mechanisms underlying its drought tolerance and adaptive responses remain largely unexplored, warranting further investigation at the molecular level.MethodsWe conducted pot-based water control experiments to subject I. stachyodes seedlings to drought stress treatments (CK, T0, T2). Root tissues from each treatment group were analyzed using transcriptomics (RNA-seq) and metabolomics (LC-MS/GC-MS) approaches to identify differentially expressed genes (DEGs) and differentially expressed metabolites (DEMs). Through integrated analysis of DEGs and DEMs, we performed KEGG pathway enrichment and constructed co-expression networks to elucidate the molecular mechanisms underlying drought stress responses in the roots of I. stachyodes seedlings.ResultsA total of 11,509 DEGs were detected in the transcriptome. Among them, the CK vs T0 group shared 7,191 DEGs, the CK vs T2 group shared 1,264 DEGs, and the T2 vs T0 group shared 3,054 DEGs. In the metabolome, a total of 622 metabolites were detected. Among them, the CK vs T0 group shared 187 DEMs, the CK vs T2 group shared 127 DEMs, and the T2 vs T0 group shared 86 DEMs. The transcriptome-metabolome analysis revealed that the roots of I. stachyodes seedlings regulate metabolic balance through the phenylpropanoid biosynthesis pathway and the flavonoid biosynthesis pathway when subjected to varying degrees of drought stress. Metabolites such as p-coumaric acid, sinapine malate, eugenol, coumestrol, medicarpin, prunin, isosakuranetin, vitexin, gallocatechin, catechin, garbunzol and dihydromyricetin, along with genes including PAL, C4H, COMT, 4CL, CHS, DFR, HIDH, I2’H, IF7GT, IF7MAT, IFR, VR, PTS and IFS are potential key substances that enable the roots of I. stachyodes seedlings to resist drought stress.DiscussionThese results elucidate that the roots of I. stachyodes seedlings can resist drought stress and adapt to drought environments by regulating the expression of genes and the synthesis of metabolites in the flavonoid and phenylpropanoid metabolic pathways, providing a foundation to facilitate the domestication of wild I. stachyodes.